Iranian interference in the Syrian crisis after 2011 and its repercussions on its political system (Raparin Journal of Humanities (RJH), 2023)
The Syrian crisis that erupted in 2011 is a pivotal development on which the future of regional and international power balances in the region depends. Because of Syria's importance in international politics due to its geographical location, at the regional and international levels, and from the geopolitical and strategic perspectives, which made it the focus of polarization for regional and global powers, as this country - Syria - became a major hub of conflict and competition between those countries. The reality of the Syrian crisis and the internal causes that led to the outbreak of this crisis in addition to identifying the motives for Iran’s intervention in the crisis and the means it followed to achieve its goals. This crisis has left great repercussions on the performance of its regime - Iran - politically, economically, and socially, and the impact of this intervention on its regional influence and its relationship with major powers. Therefore, according to the researcher's reading of the topic, this study examines the motives for Iran's intervention in the Syrian crisis after 2011 and the repercussions of this crisis on the performance of its political system.